ACADEMIC TEACHER WITH PASSION – JOB PROFESSIONALISM, COMPETENCES AND RESPONSIBILITY - Sadowska, E. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. Academic teacher in higher education is a peculiar profession. His performance of this type of mission, should also be a platform for the realization of personal passion. He requires not only in-depth knowledge and specialized competences, but also a sense of personal and collective responsibility for the education. Purpose. The goal of this paper is to examine a profile of modern academic teacher. Fulfilling the professional role of a teacher will be the main context. On the other hand, it will be a model for perception of teacher’s job in the context of calling for a professional position. Teacher, his/her passion for his job, competences and professionalism, and mostly responsibility are the platform for interaction between student and teacher. Results. The author outlines two elements of the academic teacher role: the first one is already indicated by our responsibility for shaping students, second, is to prepare students to assume responsibility for their actions. The author considers to be important the fulfillment in the two-element system approaches to build a kind of personal relationship between educating and educated. Originality. From the available sources derive information on at least 10 characteristics of a teacher is outlined in the article. The technological revolution has forced new forms of learning. In this context, the contemporary teacher should rather find themselves in the role of a guide, a mediator and helper, cooperating with students and discovering with them new ways of acquiring and sharing knowledge, using available forms and ways of communicating. This is considered to be of great importance. Conclusions. The relationship master - student, student - teacher should create a strong foundation of contemporary academic ethos. In summary, you will need at least a few times worked, upgrade and "tame with reality" his model of education. First, to highlight the desired work with the student learning outcomes, and secondly, to meet professionally and work with real passion. Thirdly, and finally, to gain confidence, to maintain authority, authority be and feel pedagogical responsibility.